HELIOS/SICRIT/mass spectrometry for analysis of aerosols in engine exhaust. Issue 8 (22nd June 2021) - Thaler, Klemens M.; Gilardi, Lorenza; Weber, Markus; Vohburger, Andreas; Toumasatos, Zisimos; Kontses, Anastasios; Samaras, Zissis; Kalliokoski, Joni; Simonen, Pauli; Timonen, Hilkka; Aurela, Minna; Saarikoski, Sanna; et al.
Abstract: Current legislations typically characterize systems of aerosols, such as from vehicle exhaust, primarily by number concentration and size distributions. While potential health threats have a dependence on the particle size, the chemical composition of particles, including the volatile and semi-volatile components adsorbed onto nonvolatile particle cores present at roadside and urban settings, is important in understanding the impact of exhaust particles on health. To date, the only tools suitable for an online in-depth chemical aerosol characterization are aerosol mass spectrometers, which are typically composed of complex and cost intensive instrumentation. We present a new analytical system, which combines a novel inexpensive infrared-radiation-based evaporation system (HELIOS) with a commercially available highly efficient atmospheric ionization source (SICRIT) connected to a rather low-price ion-trap mass spectrometer. Our inexpensive, robust and mobile aerosol characterization HELIOS/SICRIT/Mass Spectrometry system enables highly sensitive chemical analysis of particle-associated volatile substances. We validate the HELIOS/SICRIT/Mass Spectrometry system in laboratory experiments with coated particles generated under controlled conditions, and show that the system is capable of identification of combustion-generated polycyclic aromatic hydrocarbons and relative quantification of individual chemical species adsorbed on particle surfaces. We then employ our system to analyze real-world vehicle engine exhaust aerosol and show through time-resolved measurements with high time resolution (<10 s) that the chemical composition of the particles changes during different parts of an engine test cycle. Copyright © 2021 American Association for Aerosol Research